GE_GERICHTE P/2624/2022 vom 4. Mai 2023 - GE Cour de justice (2023)
ORDONNANCE DE CLASSEMENT;OBLIGATION D'ENTRETIEN;PLAINTE PÉNALE;DÉLAI;FRAIS DE LA PROCÉDURE;INDEMNITÉ(EN GÉNÉRAL) | CPP.319; CPP.427; CP.217; CPP.432; CP.31